Changes in bacterial profiles after periodontal treatment associated with respiratory quality of asthmatic children - Wiyarni Pambudi; Imelda Fabiola; Retno Indrawati; Haryono Utomo; Anang Endaryanto; Ariyanto Harsono (Indonesian Pediatric Society, 2008)
Background Despite the reduction phenomenon of asthmaexacerbation after dental plaque control, no scientific report hasbeen found to describe the link between bacterial profiles andrespiratory quality in children with asthma.Objective To investigate association between bacterial profiles changesand improvement in respiratory quality after periodontal treatment.Methods Asthmatic children with FEV1 reversibility 12% anddental plaque index 2 who qualified for inclusion criteria wererandomized into two groups. The treatment group was referred fordental plaque removal by oral biology dentist and guided to performan individual oral health care for seven days. The control groupwas observed without intervention. Each subject was assessed forrespiratory quality and bacterial profiles taken from plaque culturebefore and after one week run-in period. Paired t-test and correlationwere used for statistical anayses. The study protocol was approved bythe Medical Research Ethics Committee of Dr. Soetomo Hospital.Results Dental plaque control was performed in 18 of 36 childrenwith mild asthma. At follow-up, plaque analysis among thesubjects receiving dental treatment showed a significant reduction(P<0.01) in number of microbial colony and gram negative bacilli,corresponding by a fall in asthma score, FEV1 reversibility, andblood eosinophil (P<O.Ol). The improvement of respiratoryquality variables were moderately associated (r>0.4; P<0.05) withbacterial profiles changes after periodontal treatment.Conclusions A reduced rate of gram negative bacilli colonizationin dental plaque after periodontal treatment is related toimprovement of respiratory quality of asthmatic children.